Designing Fiber Optic Network Infrastructure with FTTX Configuration Using Network Development Life Cycle (NDLC) Method in Solok Regency - Uzma Septima; Amelia Yolanda; Dikky Chandra; Viorryn Aisha Uzhelia (Brilliance: Research of Artificial Intelligence, 2025)
In this research, the design of a GPON FTTH network using Google Earth, AutoCAD, and Optisystem applications was conducted in Nagari Rangkiang Luluih, Solok Regency. Fiber To The Home (FTTH) is a fiber optic technology architecture that delivers information from the provider to the user. The method used in this research is the Network Development Life Cycle (NDLC). The feasibility parameters used are Bit Error Ratio, Q factor, and Link Power Budget. There are 2 proposals and 2 designs for each area. From the results of the design and calculations using software, the best results were obtained for the first proposal for Nagari Rangkiang Luluih design 1 and 2, with an average Bit Error Ratio value for Downlink of 10-19 and for Uplink of 10-36, meeting the standard BER of 10-9. The Q factor values are 8.6521 for Downlink and 13.3908 for Uplink, meeting the Q factor standard of 6. And the Link Power Budget values are -19.045 for Downlink and -16.967 for Uplink, below the receiver sensitivity standard (Rx) of -28 dBm. The software calculations show that the proposed design 1 has a good network quality, is feasible, and meets the ITU-T G.984 standard. The total number of Homepassed is 234 houses or 234 ONT, 1 OLT, 4 ODC, 20 ODP for design 1 and design 2.